SOCIOLOGY 566 - POLITICAL SOCIOLOGY - Dobratz, Betty (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Political Sociology involves the study of the relationship between society and politics. This course is designed to provide graduate students with a broad understanding of the general theoretical approaches to the study of politics and to become acquainted with some of the recent literature in the field. Students should become more aware of the nature and consequences of politics and realize how politics is present in all aspects of social life.